ANTIBACTERIAL ACTION OF CERTAIN TRETINOIN AND BENZOYL PEROXIDE LIPOSOMES. CASE STUDY - Olimpia Dumitriu Buzia; Violeta Bezman; Corina Cecilia Manole Palivan; Gabi Topor; Alin Laurentiu Tatu; Earar Kamel; Grigore Ionuta (Romanian Society of Oral Rehabilitation, 2020)
The present study aims to perform a microbiological study of three pharmaceutical forms including as active substances, tretinoin and benzoyl peroxide encapsulated in liposomes, obtained in the pharmaceutical technology laboratory of the Faculty of Pharmacy of "Dunarea de Jos" University of Galati The pharmaceutical forms were tested against gram-positive and gram-negative germs and fungi. The ointment had the best antimicrobial activity in the case of gram negative bacteria (Pseudomonas aeruginosa) and gram positive bacteria (Enterococcus casseliflavus, Staphylococcus aureus) for the reference strains, as well as the strains obtained from various patients with infected supra dermatosis or acne. In the case study, including 10 patients with different degrees of acne, the liposomal products obtained had applicability, and the best-form formulation was the 0.05% tretinoin liposome gel, which also had the best results